Aksesibilitas Bagi Penyandang Disabilitas Tunanetra Dan Tunadaksa Di Kota Pekanbaru - An Nawawi, Hafiz Kemurata; Heriyanto, Meyzi; Othman, Lie (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This research was conducted because of the urgency of accessibility for persons with disabilities in buildings used for public services. Accessibility is a right that must be fulfilled by the government for people with disabilities. By providing adequate accessibility, people with disabilities will feel help, convenience and comfort in accessing public services. The purpose of this study was to investigate accessibility for blind and physically disabled persons in Pekanbaru City and identify existing barriers. The research method used is qualitative with an explanatory approach, and data is collected through observation, interviews, and document collection. This research was conducted in Pekanbaru City. The results of the study show that accessibility for blind and physically disabled persons has not yet reached an optimal level. The obstacle lies in the limitations in the development of accessibility which has not covered everything. These factors are caused by an inadequate budget, socialization that is not yet optimal, and the need for improvement in the guidance provided.